2011
DOI: 10.1016/j.cbd.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of vertebrate lipoprotein lipase: A key enzyme of very low density lipoprotein metabolism

Abstract: Lipoprotein lipase (LIPL or LPL; E.C.3.1.1.34) serves a dual function as a triglyceride lipase of circulating chylomicrons and very-low-density lipoproteins (VLDL) and facilitates receptor-mediated lipoprotein uptake into heart, muscle and adipose tissue. Comparative LPL amino acid sequences and protein structures and LPL gene locations were examined using data from several vertebrate genome projects. Mammalian LPL genes usually contained 9 coding exons on the positive strand. Vertebrate LPL sequences shared 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 109 publications
(132 reference statements)
1
17
0
Order By: Relevance
“…In addition, the phylogram suggested a sequence of gene duplication events for an ancestral PTLlike gene during vertebrate evolution (see Figure 7): (1) an ancestral PTL gene duplication generating the PTL/PLR1 and PLR2 precursor genes; (2) duplication of the vertebrate PTL/PLR1 precursor gene to form the PTL and PLR1 genes; and (3) duplication of the PLR2 gene prior to primate evolution to form the PLR2 and PLR3 genes, currently observed in primate genomes. It is also apparent that vertebrate neutral lipase genes (HL; EL; and LPL) have been generated during vertebrate evolution from a distinct ancestral gene, which is consistent with previous studies on the enzymes and genes [33][34][35][36][37].…”
Section: Phylogeny and Divergence Of Ptl-like Sequencessupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, the phylogram suggested a sequence of gene duplication events for an ancestral PTLlike gene during vertebrate evolution (see Figure 7): (1) an ancestral PTL gene duplication generating the PTL/PLR1 and PLR2 precursor genes; (2) duplication of the vertebrate PTL/PLR1 precursor gene to form the PTL and PLR1 genes; and (3) duplication of the PLR2 gene prior to primate evolution to form the PLR2 and PLR3 genes, currently observed in primate genomes. It is also apparent that vertebrate neutral lipase genes (HL; EL; and LPL) have been generated during vertebrate evolution from a distinct ancestral gene, which is consistent with previous studies on the enzymes and genes [33][34][35][36][37].…”
Section: Phylogeny and Divergence Of Ptl-like Sequencessupporting
confidence: 87%
“…The bioinformatic methodologies used in this investigation of pancreatic lipase-like genes and proteins may be also readily applied to other pancreatic proteins as well as other gene families encoding enzymes and proteins, including neutral lipases [35][36][37], acid lipases [66], carboxylesterases [67], enolases [68] and other gene families [69][70][71].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of three members of the TG lipase family, LPL could contribute to the process of TG-rich CMs and VLDLs (Holmes et al, 2011), and in the removal of lipoproteins from the circulatory system (Murthy et al, 1996). In adult sheep, Pethick and Dunshea (1993) found that about 55-60% of the total amount of free fatty acids originate from hydrolysis of circulating triacylglycerols by LPL.…”
Section: Discussionmentioning
confidence: 99%
“…The bovine LPL gene maps to chromosome 8 and its coding region consists of 10 exons, which are highly expressed in skeletal muscle and adipose tissue (Holmes et al, 2011). Wang et al (2012) identified two polymorphisms (T355420C and A355427T) of the LPL gene that were associated with growth traits in Xiangxi cattle.…”
Section: Introductionmentioning
confidence: 99%